Perceptual awareness of near-threshold tones scales gradually with auditory cortex activity and pupil dilation - Doll, Laura; Dykstra, Andrew R.; Gutschalk, Alexander (iScience, 2024)
Negative-going responses in sensory cortex co-vary with perceptual awareness of sensory stimuli. Given that this awareness negativity has also been observed for undetected stimuli, some have challenged its role for perception. To address this question, we combined magnetoencephalography, electroencephalography, and pupillometry to study how sustained attention and response criterion affect the auditory awareness negativity. Participants first detected distractor sounds and denied hearing task-irrelevant near-threshold tones, which evoked neither awareness negativity nor pupil dilation. These same tones evoked both responses when task-relevant, stronger for hit but also present for miss trials. Participants then rated their perception on a six-point scale to test whether response criterion explains the presence of these responses for miss trials. Decreasing perception ratings were associated with gradually reduced evoked responses, consistent with signal detection theory. These results support the concept of an awareness negativity that is modulated by attention, but does not require a non-linear threshold mechanism.
Gesehen am 18.07.2024